The Effectiveness of Sleep Hygiene on Sleep Quality in Patients with Congestive Heart Failure: A Randomized Controlled Trial Study - Lofa, Priyo Hadi Prasetiyo; Yunitri, Ninik; Rayasari, Fitrian; Azzam, Rohman; Kurniasih, Dian Noviati (PT Inovasi Pratama Internasional, 2024)
Good sleep quality in congestive heart failure (CHF) patients helps repair heart muscle cells. Sleep hygiene is one of the non-pharmacological interventions to overcome sleep disorders. This study aims to determine the effectiveness of sleep hygiene on sleep quality in CHF patients. A Randomized Controlled Trial (RCT) with two groups was taken using probability sampling with block random sampling method. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) and sleep habits using the Sleep Hygiene Index (SHI). Outputs were measured based on the change in the mean between the measurement time using the paired t-test and the difference in the mean between groups using the independent t-test. A total of 30 respondents were involved in this study. The intervention group showed a significant improvement in sleep quality after sleep hygiene therapy with a mean difference (MD) of 4.20 (SE=0.70; p-value=<0.01). Sleep quality between the two groups showed a significantly greater difference in the intervention group than in the control group (MD=-2.13, SE=1.00, p-value=0.04, effect size (Cohens'd)=-0.77). Sleep hygiene is a non-pharmacological intervention that effectively improves sleep quality in patients with CHF.